Smartphone video games for cognitive functions and negative symptoms in male with chronic schizophrenia: A randomized controlled trial - Wenhui Wang; Mengting Ye; Yongjie Zhong; Miaomiao Zhang; Yue Wang; Chuanchuan Chen; Yitan Yao; Ziqiao Feng; Xiaoping Yuan; Shenya Shi; Xiaoqin Zhou; Kai Zhang (Heliyon)
Background: Video games have been extensively examined as a promising and innovative approach for addressing various psychiatric disorders. The primary objective of this study is to evaluate the effect of smartphone video games on cognitive functions, psychiatric symptoms and overall functioning in male with chronic schizophrenia. Methods: We conducted a 6-week randomized controlled trial to compare the cognitive function, psychotic symptoms, overall functioning, and other outcomes of schizophrenic patients who engaged in smartphone video games (game group) with those who watched television programs (control group). We recruited schizophrenic patients who met the eligibility criteria from July 2021 to February 2022. The primary outcomes were the comparisons of various clinical scores between the two groups at baseline before interventions, the third and sixth weeks of the interventions, and the third and sixth weeks following the completion of interventions. Results: Comparing the scores of the RBANS, PANSS, and GAF scales between the two groups, smartphone video games improved cognitive function, negative symptoms, and overall functioning. However, GSE and PHQ-9 scores did not reveal significant differences between the two groups. While there was a significant difference in PMGQ scores between the two groups, neither group reached the threshold for game addiction. Conclusions: In this study, we emphasize the improvements of cognitive functions, psychiatric symptoms and overall functioning that brought by smartphone video games in male with chronic schizophrenia. Our findings indicate the need for more extensive research, future research should address what mechanisms of action underlie these effects of video games. Trial registration: This study was registered in the Chinese Clinical Trial Registry (ChiCTR2100044113) and registered on 11/3/21.